One thing I learned this week was how to solve systems using substitution.
The first step to solving systems using substitution is to find the two equations you’re trying to solve.
The next step is to pick one equation and isolate the x or y.
x+5y=-5 -> x=-5y-5
The next step is to substitute that equation you just isolated into the other equation using brackets.
x-2y=6 -> (-5y-5)-2y=6
The next step is to solve the equation.
(-5y-5)-2y=6 -> -7y=6+5 -> 7y=11
The next step is to substitute the number just found back into the rearranged equation.
Answer: (2.9, 1.6)